Mechanical exfoliation and electrical characterization of a one-dimensional Nb2Se9 atomic crystal. Issue 66 (9th November 2018) - Kim, Bum Jun; Jeong, Byung Joo; Oh, Seungbae; Chae, Sudong; Choi, Kyung Hwan; Nasir, Tuqeer; Lee, Sang Hoon; Kim, Kwan-Woo; Lim, Hyung Kyu; Choi, Ik Jun; Chi, Linlin; Hyun, Sang-Hwa; et al.
Abstract : A novel semiconductor 1D nanomaterial, Nb2 Se9, was synthesized on a bulk scale via simple vapor transport reaction between niobium and selenium. Abstract : A novel semiconductor 1D nanomaterial, Nb2 Se9, was synthesized on a bulk scale via simple vapor transport reaction between niobium and selenium. Needle-like single crystal Nb2 Se9 contains numerous single Nb2 Se9 chains linked by van der Waals interactions, and we confirmed that a bundle of chains can be easily separated by mechanical cleavage. The exfoliated Nb2 Se9 flakes exhibit a quasi-two-dimensional layered structure, and the number of layers can be controlled using the repeated-peeling method. The work function varied depending on the thickness of the Nb2 Se9 flakes as determined by scanning Kelvin probe microscopy. Moreover, we first implemented a field effect transistor (FET) based on nanoscale Nb2 Se9 flakes and verified that it has p-type semiconductor characteristics. This novel 1D material can form a new family of 2D materials and is expected to play important roles in future nano-electronic devices.